"Accountability" in interaction-focused intervention for aphasia: a conversation-analytic study of therapeutic effects. Issue 2 (1st February 2019) - Barnes, Scott
ABSTRACT: Background : Aphasia interventions typically require independent practice on the part of people with aphasia. Interaction-focused interventions aim to change patterns in everyday conversation, and require both people with aphasia and their familiar communication partners to implement communication strategies. Little empirical evidence is available on how people with aphasia and their conversation partners practice communication strategies independently. Aims : This study explores how people with aphasia and their conversation partners attend to intervention goals during independent conversations. It focuses on how people with aphasia are made "accountable" for using communication strategies. Methods & Procedures : This study employed a descriptive, qualitative design, drawing on single-case conversation analytic methods. Six participants (three people with aphasia, and their respective spouses) recorded communication samples as part of an interaction-focused intervention. About 22 min of these samples were transcribed and analysed using conversation-analytic methods. Outcomes & results : 27 instances where conversation partners topicalised intervention were analysed. The extracts presented, demonstrate that intervention goals were invoked via a range of communicative acts, including repair initiations, assessments, and directive-like assertions. People with aphasia were treated as responsible for not administering strategies at communicatively relevant moments. Conclusions : Intervention participants' displays of "online" reasoning about intervention goals may be practically important for interaction-focused intervention, and warrant further attention. These displays hold potential for better defining therapeutic mechanisms in interaction-focused intervention.